Elizabeth Schuyler Hamilton in psychobiography: Sense of coherence and faith across her lifetime - Mayer, Claude-Hélène (Frontiers in Psychology, 2022)
This article focuses on the coping skills of one selected, extraordinary woman, Elizabeth Schuyler Hamilton (1757–1854) during the founding of the United States of America. This work contributes to theory on two different levels. First, it contributes to psychobiographical research on women in diverse spheres of society, thereby strengthening the aspect of gender and coping strategies in terms of psychobiographical perspectives. Second, it contributes to theory-building in psychobiographical research anchored in positive psychology, promoting the idea that a multiplicity (crystallisation) of theories should be used to explore and analyse the lifespan of extraordinary individuals. The psychobiography responds to the question how Elizabeth Schuyler Hamilton coped with life’s challenges and tragedies through the lenses of sense of coherence and faith development theory. The article uses a psychobiographical case study design within the research paradigm of modern hermeneutics. First- and third-person data on the subject were collected and evaluated through thematic analysis, including articles, documentation, letters, film material, and political scripts. Customary ethical standards for psychobiographical research were followed, thereby ensuring an ethical, respectful, empathetic and accountable research approach. The article presents findings on the coping skills, sense of coherence, and faith development in the life of Elizabeth Schuyler Hamilton which strongly influenced her resilience and support for others during her long and extraordinary life. Conclusions are drawn with regard to the way women cope in different sociocultural, sociopolitical and socio-economic spheres using historical and contemporary retrospectives. Recommendations are provided for future psychobiographical research on women in diverse contexts and in psychobiographical, gendered practice.